Inventing atmospheric science : Bjerknes, Rossby, Wexler, and the foundations of modern meteorology - Fleming, James Rodger (MIT Press, 2016)
"This big picture history of atmospheric research examines the first six decades of the twentieth century, from the dawn of applied fluid dynamics to the emergence, by 1960, of the interdisciplinary atmospheric sciences. Using newly available archival sources, it documents the work of three interconnected generations of scientists: Vilhelm Bjerknes, Carl-Gustaf Rossby, and Harry Wexler, whose aspirations were fueled by new theoretical insights, pressing societal needs, and expanded technological capabilities. Radio, radar, aviation, nuclear tracers, digital computing, sounding rockets, and satellites provided new ways to measure and study the global atmosphere -- a huge and dauntingly complex system. Bjerknes brought us a fundamental circulation theorem and founded the Bergen school of weather forecasting; Rossby established the graduate schools of meteorology at M.I.T., Chicago, and Stockholm, which focused on upper-air dynamics and, after 1947, on atmospheric environmental issues; and Wexler brought all the new technologies into the U.S. Weather Bureau and, with his colleague Jule Charney, prepared the foundations for the emergence of the interdisciplinary atmospheric sciences. This history weaves together cold war studies, military history, the rise of government research and development, and aviation and aeronautics with a nascent global awareness. It is a fascinating history of something we all experience--the weather --told through compelling historical characters"--Provided by publisher